Trans Care - Malatino, Hil (Forerunners (Minneapolis, Minn.), 2020)
A radical and necessary rethinking of trans care. What does it mean for trans people to show up for one another, to care deeply for one another? How have failures of care shaped trans lives? What care practices have trans subjects and communities cultivated in the wake of widespread transphobia and systemic forms of trans exclusion? Trans Care is a critical intervention in how care labor and care ethics have been thought, arguing that dominant modes of conceiving and critiquing the politics and distribution of care entrench normative and cis-centric familial structures and gendered arrangements. A serious consideration of trans survival and flourishing requires a radical rethinking of how care operates. Forerunners is a thought-in-process series of breakthrough digital works. Written between fresh ideas and finished books, Forerunners draws on scholarly work initiated in notable blogs, social media, conference plenaries, journal articles, and the synergy of academic exchange. This is gray literature publishing: where intense thinking, change, and speculation take place in scholarship.